Efectos en la salud asociados a los fertilizantes orgánicos en los agricultores de la Parroquia San José de Chaltura. - Imbaquingo Manrique, Milton Daniel (2025)
This research aimed to apply a communitarian guide to diminish the direct effects on the health of farmers produced by the use of fertilizers in San Jose de Chaltura Parish, focused on determining the most common conditions of health associated with the use of these products, as well as the relationship between its exposure and the development of health problems, thus identifying complications such as cutaneous infections, respiratory and gastric-intestinal diseases caused by the exposure to pathogenic microorganisms and suspended particles; given these conditions, it was promoted the improvement of health among farmers, and to this purpose the methodology used was the quantitative paradigm, in addition to the empiric method, and the scientific observation which was the mechanism to gather accurate and reliable data regarding the existing problem under study. For the analysis and obtaining the results, a Likert scale was used whose results showed that 80% of the population have not received any training about the use of fertilizers, 62% do not know the health effects that are caused by the use of fertilizers, regarding security measures 47% claimed to wear masks which represent a lower percentage with the use of other implements, 60% of the population have suffered diseases, 58% rarely attend to medical appointments when they get sick, 29% claimed to always attend to medical appointments and 13% responded they never attend to medical controls; all these previous indicators were determining to intervene in the health of the population under this research and thus improve their conditions of life.